Evaluating the vulnerability of coralligenous epifauna to macroalgal invasions. Issue 9 (22nd June 2021) - Navarro‐Barranco, Carlos; Moreira, Juan; Espinosa, Free; Ros, Macarena; Rallis, Ioannis; Sempere‐Valverde, Juan; Ostalé‐Valriberas, Enrique; Altamirano, María; García‐Gómez, J. Carlos; Guerra‐García, José M.
Abstract: This work constitutes the first comprehensive study of the epifaunal response to biological invasions in coralligenous habitats, which are one of the main hotspots of biodiversity in the Mediterranean. The epifaunal community inhabiting the invasive macroalga Rugulopteryx okamurae and other dominant sessile hosts on coralligenous habitats (i.e. the sponge Spongia lamella, the gorgonian Paramuricea clavata, and the macroalga Sphaerococcus coronopifolius ) was characterized. A total of 137 taxa were found. There was a lack of functional equivalence between macroalgal species (both native and invasive) and sessile invertebrates. Despite the absence of significant differences in mean density values and number of species per replicate among host species, epifaunal composition on gorgonians and sponges differed significantly from that on both macroalgae. Epifaunal assemblages, especially those inhabiting macroalgal species, were dominated by generalist detritivorous species that can inhabit different hosts, while specialized interactions between mobile epifauna and sessile hosts were observed almost exclusively on sessile invertebrates. Moreover, epifaunal community associated with invertebrate hosts showed higher spatial heterogeneity in comparison with native and invasive macroalgae. A competitive displacement of native hosts by the spreading of R. okamurae on coralligenous habitats would likely result in a biotic impoverishment in terms of overall number of species and a taxonomical and functional homogenization of the epifaunal community. Specialist species with a heterogeneous distribution could be gradually replaced by a spatially homogeneous assemblage dominated by generalist species.